Experimental investigation of mechanical properties and morphology of bamboo-glass fiber-nanoclay reinforced epoxy hybrid composites - Syed Mansoor Ahmad; Gowrishankar M C; Manjunath Shettar; Sathyashankara Sharma (Cogent Engineering, 2023)
AbstractIn the present work, the mechanical and morphological characterization of bamboo-glass fiber-nanoclay epoxy hybrid composites is carried out. Materials are prepared using a hand lay-up process with different wt.% of bamboo fiber, glass fiber, nanoclay, and epoxy. As per ASTM standards, fabricated composite laminates are cut and tested for tensile and flexural properties. The bamboo fiber epoxy composites (BFEC) display the tensile and flexural strength of 137 and 170 MPa, respectively. Hybrid composites, viz. bamboo-glass fibers epoxy composites (BGFEC), display improved tensile (180–240 MPa) and flexural (225 to 320 MPa) strengths compared to BFECs. Glass fiber epoxy composites (GFEC) display maximum tensile (265 MPa) and flexural (360 MPa) strengths among all the composites. Furthermore, the addition of nanoclay improves the tensile (by 6 to 8%) and flexural (by 8 to 10%) strengths of epoxy, BFEC, BGFEC, and GFECs. SEM analysis is conducted for fractured tensile specimens to understand the reasons for specimen failure.